196k views
3 votes
Select all that apply.

If 2x2-6x=0, then
2x = 0
OX-6 = 0
a
X-3 = 0
x + 1 = 0

2 Answers

3 votes

Answer:

x = 3

x = 0

Explanation:

The correct answer is

x = 3

x = 0.

Steps below.

Pulling out like terms

Theory - Roots of a product

Solving a Single Variable Equation

Two answers were found

Hope this helps.

User IrishGringo
by
5.9k points
3 votes

Answer:

2x =0 x-3 =0

Explanation:

2x^2-6x=0

Factor out 2x

2x( x-3) = 0

Using the zero product property

2x =0 x-3 =0

User Lukaszrys
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.